Respuesta :
[tex]\dfrac{\csc^2x-1}{1+\sin x}=\dfrac{\cot^2x}{1+\sin x}[/tex]
which comes from the fact that [tex]\sin^2x+\cos^2x=1\implies1+\cot^2x=\csc^2x[/tex].
[tex]\dfrac{\cot^2x}{1+\sin x}\times\dfrac{1-\sin x}{1-\sin x}=\dfrac{\cot^2x(1-\sin x)}{1-\sin^2x}=\dfrac{\cot^2x(1-\sin x)}{\cos^2x}[/tex]
Now, [tex]\cot x=\dfrac{\cos x}{\sin x}[/tex], which means
[tex]\dfrac{\cot^2x(1-\sin x)}{\cos^2x}=\dfrac{\frac{\cos^2x}{\sin^2x}(1-\sin x)}{\cos^2x}=\dfrac{\frac1{\sin^2x}(1-\sin x)}1=\dfrac{1-\sin x}{\sin^2x}[/tex]
Recalling that [tex]\csc x=\dfrac1{\sin x}[/tex], you can write this as
[tex]\dfrac1{\sin^2x}-\dfrac{\sin x}{\sin^2x}=\csc^2x-\dfrac1{\sin x}=\csc^2x-\csc x[/tex]
which comes from the fact that [tex]\sin^2x+\cos^2x=1\implies1+\cot^2x=\csc^2x[/tex].
[tex]\dfrac{\cot^2x}{1+\sin x}\times\dfrac{1-\sin x}{1-\sin x}=\dfrac{\cot^2x(1-\sin x)}{1-\sin^2x}=\dfrac{\cot^2x(1-\sin x)}{\cos^2x}[/tex]
Now, [tex]\cot x=\dfrac{\cos x}{\sin x}[/tex], which means
[tex]\dfrac{\cot^2x(1-\sin x)}{\cos^2x}=\dfrac{\frac{\cos^2x}{\sin^2x}(1-\sin x)}{\cos^2x}=\dfrac{\frac1{\sin^2x}(1-\sin x)}1=\dfrac{1-\sin x}{\sin^2x}[/tex]
Recalling that [tex]\csc x=\dfrac1{\sin x}[/tex], you can write this as
[tex]\dfrac1{\sin^2x}-\dfrac{\sin x}{\sin^2x}=\csc^2x-\dfrac1{\sin x}=\csc^2x-\csc x[/tex]
Answer: trigonometric identities
1 C sin^2
2 B csc x(csc x-1)
3 D 1-sin theta/ csc theta
4 D tan x sin x
5 A cos x cot2 x